Plant-Based Diet - Modulation of the Gut Microbiome and Metabolic Consequences - Wróbel, Bartosz; Wójcik, Lena; Filipski, Michał; Klonowska, Justyna; Kosek, Szymon (Quality in Sport, 2026)
Plant-based diets have gained prominence due to their environmental benefits and protective effects against metabolic disorders, including obesity, type 2 diabetes, and cardiovascular disease. The gut microbiome acts as a key metabolic organ mediating the interaction between diet and host physiology, primarily through microbiota-accessible carbohydrates (MACs) and polyphenols found abundantly in plant foods. A comprehensive literature review demonstrates that plant-based diets promote favourable shifts in microbiota composition, increasing beneficial bacteria populations such as Lachnospiraceae, Ruminococcaceae, and Bifidobacterium spp., while reducing pathobionts including Enterobacteriaceae and Bilophila wadsworthia. These compositional changes enhance production of short-chain fatty acids, particularly butyrate, which strengthen intestinal barrier function and activate signalling pathways regulating satiety hormones (GLP-1, PYY) and glucose homeostasis. Plant-derived tryptophan metabolites and urolithin A further support intestinal integrity through aryl hydrocarbon receptor and Nrf2 pathway activation. The resulting microbiome alterations correlate with improved postprandial glycemic response, reduced cholesterol levels, decreased inflammatory markers, and lower risk of non-alcoholic fatty liver disease. However, the protective effects depend critically on consuming whole foods rich in fiber and polyphenols rather than processed plant-based alternatives. Long-term randomized controlled trials and personalized approaches considering individual microbiome variation are necessary to fully elucidate these mechanisms and optimize dietary recommendations across diverse populations.